Availability Of Services and Facilities at Primary Health Centers in Ahmedabad District, Gujarat - Shah , Rakesh; Bhavsar , BS; Nayak , Sunil; Goswami , Mihir (National Journal of Community Medicine, 2010)
This cross-sectional study conducted among 10 randomly selected PHCs of Ahmedabad district in 2006 revealed existence of vacant staff deficits ranging from 11.3% to 30%; significant staff residing >30 Kms away from the facility; inadequate public transport system for patients; inadequate supplies, POL and functional PHC vehicle; and, bed paucity. The study reveals the necessity for suitable strengthening of these PHCs in line with their envisaged role in health care delivery in line with our national guidelines.